PERANAN MOTIVASI BERPRESTASI DAN KECEMASAN SOSIAL TERHADAP KEPERCAYAAN DIRI PADA ATLET TAEKWONDO SAAT BERTANDING DI KABUPATEN PASURUAN - Aguardien Puristin Banafsaj; Ghozali Rusyid Affandi (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
This study aims to find out the results of the role between achievement motivation and social anxiety on self confidence in athletes when competing in pasuruan regency. Confidence can lead to the belief that within a person has the ability. The research method uses correlational. Data collection used a questionnaire with a population of 200 athletes and 154 athletes used as respondents. Sampling was taken using accidental sampling cited by Sugiyono. The reliability test uses the Alpha Cronbach method with a standard > 0.6. The analysis technique uses multiple regression with the help of JASP 0.16. Research results: (1) the effect of athlete’s achievement motivation on self confidence gets a score of 11.4% positively and significantly (2) the effect of athlete’s social anxiety on self confidence gets a score of 17.5% positivelyand significantly (3) the effect of achievement motivation, social anxiety on self confidence gets a score of 37.5% positively and significantly.